Knowledge management and acquisition for intelligent systems : 15th Pacific Rim Knowledge Acquisition Workshop, PKAW 2018, Nanjing, China, August 28-29, 2018, Proceedings /: 15th Pacific Rim Knowledge Acquisition Workshop, PKAW 2018, Nanjing, China, August 28-29, 2018, Proceedings. (2018) - Unknown
No abstract available